2013
DOI: 10.3402/jev.v2i0.21927
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular membrane vesicles from umbilical cord blood‐derived MSC protect against ischemic acute kidney injury, a feature that is lost after inflammatory conditioning

Abstract: BackgroundMesenchymal stromal cells (MSC) are shown to have a great therapeutic potential in many immunological disorders. Currently the therapeutic effect of MSCs is considered to be mediated via paracrine interactions with immune cells. Umbilical cord blood is an attractive but still less studied source of MSCs. We investigated the production of extracellular membrane vesicles (MVs) from human umbilical cord blood derived MSCs (hUCBMSC) in the presence (MVstim) or absence (MVctrl) of inflammatory stimulus.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
116
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(123 citation statements)
references
References 86 publications
4
116
0
3
Order By: Relevance
“…Expression of HLA-II molecules in MSCs would trigger the activation of the host's innate immune system which in turn would impede their potential immunomodulatory effect. In fact, it has been suggested that the increased HLA expression in EVs from umbilical cord blood-derived MSCs after treatment with IFNγ may be responsible of the loss of their protective effect against ischemic acute kidney injury 31. Given that our results suggest that non-primed UCMSCs are as potent as primed MSCs in regulating T cell responses, we would consider using non-primed cells in therapeutic approaches.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Expression of HLA-II molecules in MSCs would trigger the activation of the host's innate immune system which in turn would impede their potential immunomodulatory effect. In fact, it has been suggested that the increased HLA expression in EVs from umbilical cord blood-derived MSCs after treatment with IFNγ may be responsible of the loss of their protective effect against ischemic acute kidney injury 31. Given that our results suggest that non-primed UCMSCs are as potent as primed MSCs in regulating T cell responses, we would consider using non-primed cells in therapeutic approaches.…”
Section: Discussionmentioning
confidence: 82%
“…MSCs have been described to suppress the immune response affecting T cell proliferation and polarization, to induce regulatory T cells, and to module Antigen Presenting Cells (APCs) 11,31-34. In our settings, UCMSCs were confirmed to have potent suppressive capabilities on T cell proliferation, but whereas IFNγ conditioning enhances immunosuppressive functions of both bone marrow- and adipose tissue-derived MSCs 7,9,35, no differences were found comparing IFNγ-primed to non-primed UCMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…MSC-derived EV biogenesis has been shown to be regulated by cross-talk between MSC and their surrounding microenvironment. Thus, extracellular conditions, such as hypoxia or inflammation, influence molecular packaging into EVs, and impact their functional properties[54, 55]. Both exosomes and microvesicles interact with their target cells via either ligand-receptor signaling pathways or internalization by phagocytosis, endocytosis, and direct membrane fusion (Figure 2).…”
Section: Mesenchymal Stem Cells Extracellular Vesicles For Acute Lmentioning
confidence: 99%
“…Overall, MVs were found to mimic the beneficial effects of MSCs, modulating T-cells as well as innate immune cell functions[54]. The effects appeared to be mediated in part by the transfer of RNA by MSC MVs to the injured renal epithelium, as indicated by the loss of reparative effects after RNase pretreatment of the MVs[40, 69, 72].…”
Section: Mesenchymal Stem Cells Extracellular Vesicles For Acute Lmentioning
confidence: 99%
“…Another interesting finding is that MSC-MV change their content depending on the environment in which they are cultured; Kilpinen et al [12] compared MSC-conditioned media in the presence or absence of interferon-γ mimicking an inflammatory microenvironment. They compared the ability of MSC to protect rats from reperfusion injury in vivo; while the MSC cultured under normal conditions had a protective effect on kidney function, this effect was abrogated when the cells were cultured in the presence of interferon-γ.…”
Section: Mechanisms Of Msc Protection Against Acute Kidney Injurymentioning
confidence: 99%